Ambulatory Care Access and Postdischarge Adverse Events after Emergency Department Visits Among Medicare Beneficiaries - Lin, M. (Health Serv Res, 2020)
RESEARCH OBJECTIVE: Numerous clinical guidelines endorse timely follow‐up after an emergency department (ED) visit as a quality indicator. However, there are little data on how often ambulatory follow‐up care after an ED visit occurs, and whether follow‐up rates are associated with adverse events. STUDY DESIGN: We used Medicare data to identify ED visits from 2011 to 2016. We limited our sample to patients discharged from the ED (did not die and were not admitted, kept for observation, or transferred). We excluded patients discharged to a nursing facility or rehabilitation center. Our primary outcomes were percentage of visits with any non‐ED ambulatory follow‐up visit within 7 and 30 days overall and stratified by beneficiary characteristics (age, sex, race, Medicaid eligibility) and principal visit diagnosis category (38 categories designed for emergency care health services research). We calculated the rates of the following postdischarge events at 7 and 30 days: mortality, repeat ED visits, and hospitalizations both overall and stratified by patient characteristics and visit diagnosis. POPULATION STUDIED: Continuously enrolled Medicare beneficiaries aged 65 and older in 2011‐2016. PRINCIPAL FINDINGS: There were 9,513,672 ED visits in our sample. There was a 40.3% rate of ambulatory follow‐up within 7 days, and 70.7% within 30 days. Male beneficiaries had lower rates of ED utilization (39% of all ED visits in our sample), and lower rates of 30‐day follow‐up (69.4% vs. 71.4% among female beneficiaries). Men had higher rates of postdischarge mortality (1.7% vs. 1.2%), repeat ED visits (18.3% vs. 16.8%), and hospitalizations (10.1% vs. 9.1%) compared with women at 30 days. Compared with beneficiaries not eligible for Medicaid, Medicaid‐eligible beneficiaries had lower rates of follow‐up at 7 days (32.0% vs. 42.6%) and 30 days (62.9% vs. 72.9%), yet they had higher rates of postdischarge mortality (1.5% vs. 1.4%), repeat ED visits (23.5% vs. 15.7%), and hospitalizations (11.2% vs. 9.0%) at 30 days. White beneficiaries had the highest rates of follow‐up at 7 days (41.4%) and 30 days (71.6%), while black beneficiaries had the lowest rates of follow‐up at 7 days (32.6%) and 3 days (64.7%). After 30 days, white beneficiaries had the highest rates of mortality after discharge (1.5% vs 1.2% among black and 1.0% among Hispanic beneficiaries), while black beneficiaries had the highest rates of postdischarge ED visits (20.8%) and hospitalizations (10.0%). Among diagnosis categories, visits for dysrhythmias had the highest rate of ambulatory follow‐up at 30 days (80.5%), while visits for mental illness had the lowest rates of 30‐day follow‐up (60.5%). CONCLUSIONS: Nearly 30% of traditional Medicare beneficiaries discharged from the ED had no ambulatory follow‐up within 30 days. Medicaid‐eligible beneficiaries had lower rates of follow‐up and higher rates of postdischarge mortality and acute care utilization. Beneficiaries with a visit for a mental health condition had the lowest rate of follow‐up at 30 days. IMPLICATIONS FOR POLICY OR PRACTICE: There appear to be significant barriers to outpatient follow‐up for vulnerable Medicare beneficiaries using the ED. Our findings underscore the barriers to access outside of insurance; targeted efforts are needed for beneficiaries at the highest risk of adverse outcomes. PRIMARY FUNDING SOURCE: This study was supported by the Emergency Medicine Foundation.